PENGARUH AUDIT INTERNAL DALAM UPAYA PENCEGAHAN KORUPSI (STUDI LITERATUR) (JEB17 : Jurnal Ekonomi dan Bisnis, 2024)
This research is to review the important role of internal audit in corruption prevention. Internal audit is identified as a key instrument for identifying corruption gaps and risks within organizations. This research explores how internal audit practices, including compliance evaluation, transaction monitoring, and internal control implementation, can effectively reduce opportunities for corruption. The purpose of this study is to establish hypotheses regarding the influence between variables that will be used in future research. The results of this study conclude that high pressure, opportunity, and rationalization increase the incidence of corruption and internal audit does not work effectively in preventing corruption.